Lisocabtagene maraleucel versus standard of care with salvage chemotherapy followed by autologous stem cell transplantation as second-line treatment in patients with relapsed or refractory large B-cell lymphoma (TRANSFORM): results from an interim analysis of an open-label, randomised, phase 3 trial. Issue 10343 (18th June 2022) - Kamdar, Manali; Solomon, Scott R; Arnason, Jon; Johnston, Patrick B; Glass, Bertram; Bachanova, Veronika; Ibrahimi, Sami; Mielke, Stephan; Mutsaers, Pim; Hernandez-Ilizaliturri, Francisco; Izutsu, Koji; Morschhauser, Franck; et al.
Summary: Background: Patients with large B-cell lymphoma (LBCL) primary refractory to or relapsed within 12 months of first-line therapy are at high risk for poor outcomes with current standard of care, platinum-based salvage immunochemotherapy and autologous haematopoietic stem cell transplantation (HSCT). Lisocabtagene maraleucel (liso-cel), an autologous, CD19-directed chimeric antigen receptor (CAR) T-cell therapy, has previously demonstrated efficacy and manageable safety in third-line or later LBCL. In this Article, we report a prespecified interim analysis of liso-cel versus standard of care as second-line treatment for primary refractory or early relapsed (within 12 months after response to initial therapy) LBCL. Methods: TRANSFORM is a global, phase 3 study, conducted in 47 sites in the USA, Europe, and Japan, comparing liso-cel with standard of care as second-line therapy in patients with primary refractory or early (≤12 months) relapsed LBCL. Adults aged 18–75 years, Eastern Cooperative Oncology Group performance status score of 1 or less, adequate organ function, PET–positive disease per Lugano 2014 criteria, and candidates for autologous HSCT were randomly assigned (1:1), by use of interactive response technology, to liso-cel (100 × 10 6 CAR + T cells intravenously) or standard of care. Standard of care consisted of three cycles of salvage immunochemotherapy delivered intravenously—R-DHAP (rituximab 375 mg/m 2 on day 1, dexamethasone 40 mg on days 1–4, two infusions of cytarabine 2000 mg/m 2 on day 2, and cisplatin 100 mg/m 2 on day 1), R-ICE (rituximab 375 mg/m 2 on day 1, ifosfamide 5000 mg/m 2 on day 2, etoposide 100 mg/m 2 on days 1–3, and carboplatin area under the curve 5 [maximum dose of 800 mg] on day 2), or R-GDP (rituximab 375 mg/m 2 on day 1, dexamethasone 40 mg on days 1–4, gemcitabine 1000 mg/m 2 on days 1 and 8, and cisplatin 75 mg/m 2 on day 1)—followed by high-dose chemotherapy and autologous HSCT in responders. Primary endpoint was event-free survival, with response assessments by an independent review committee per Lugano 2014 criteria. Efficacy was assessed per intention-to-treat (ie, all randomly assigned patients) and safety in patients who received any treatment. This trial is registered with ClinicalTrials.gov, NCT03575351, and is ongoing. Findings: Between Oct 23, 2018, and Dec 8, 2020, 232 patients were screened and 184 were assigned to the liso-cel (n=92) or standard of care (n=92) groups. At the data cutoff for this interim analysis, March 8, 2021, the median follow-up was 6·2 months (IQR 4·4–11·5). Median event-free survival was significantly improved in the liso-cel group (10·1 months [95% CI 6·1–not reached]) compared with the standard-of-care group (2·3 months [2·2–4·3]; stratified hazard ratio 0·35; 95% CI 0·23–0·53; stratified Cox proportional hazards model one-sided p<0·0001). The most common grade 3 or worse adverse events were neutropenia (74 [80%] of 92 patients in the liso-cel group vs 46 [51%] of 91 patients in the standard-of-care group), anaemia (45 [49%] vs 45 [49%]), thrombocytopenia (45 [49%] vs 58 [64%]), and prolonged cytopenia (40 [43%] vs three [3%]). Grade 3 cytokine release syndrome and neurological events, which are associated with CAR T-cell therapy, occurred in one (1%) and four (4%) of 92 patients in the liso-cel group, respectively (no grade 4 or 5 events). Serious treatment-emergent adverse events were reported in 44 (48%) patients in the liso-cel group and 44 (48%) in the standard-of-care group. No new liso-cel safety concerns were identified in the second-line setting. There were no treatment-related deaths in the liso-cel group and one treatment-related death due to sepsis in the standard-of-care group. Interpretation: These results support liso-cel as a new second-line treatment recommendation in patients with early relapsed or refractory LBCL. Funding: Celgene, a Bristol-Myers Squibb Company.